José María Valverde, Antonio Colinas, Rafael Argullol, Antoni Man, JaimeSiles: Diálogos sobre poesía española, ed. de Nieves Trabanco. - Paulino, José (Dicenda. Estudios de lengua y literatura españolas, 1995)
Sin resumen